The Ethnoeconomic Assessment of Mina Rice Farming Development in South Konawe District - Samsul Alam Fyka; Usman Rianse; Lukman Yunus; Muhammad Aswar Limi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research examines the ethnoeconomics of Mina Padi farming development in the lebak swamplands with a focus on the local wisdom of the Bugis community. The aim was to understand the economic value and benefits that farmers gain through this practice. The research took place from March 2023 to February 2024 and involved 75 Mina Padi farmers and key informants such as village heads and farmer group leaders. Data were collected through in-depth interviews, field observations, and documentation. The approach used was mixed methods, combining qualitative and quantitative analyses within an ethnoeconomic framework to explore the economic, social, and cultural dimensions of Mina Padi farming. The results showed that farmers have inherited traditional rice and fish farming knowledge from their ancestors, which is now combined with modern technology. This process includes land cultivation, planting, maintenance, and post-harvesting, which is carried out with attention to ecological and economic aspects. Economically, Mina Padi farming provides important benefits in income diversification and food security for farming families through fish and rice supplies. This research confirms that the collaboration between local wisdom and modern technology has great potential to improve farmers' welfare and agricultural sustainability in lebak swamplands. The findings are expected to be valuable inputs for policymakers and sustainable agricultural development programs.